PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN MODERASI KECERDASAN INTELEKTUAL PADA PERUSAHAAN CV. GREEN ANGELICA - Yulieasih, Mutiara; Purwanto, Purwanto (Universitas 17 Agustus 1945 Surabaya, 2019)
This study aims to determine and analyze the influence of transformational leadership style and motivation on employee performance with moderation of intellectual intelligence in the company CV. Green Angelica. The location of this research is the company CV. Green Angelica Jl. Ngagel Wasana III No. 75 Surabaya. The sample used in this study was 80 people. Researchers used quantitative descriptive analysis using SPSS version 20 for windows. The results showed that intellectual intelligence did not moderate the transformational leadership style on employee performance at the company CV. Green Angelica does not have a significant effect of 0.870 which means the company must maintain existing conditions and improve these conditions towards a better, while intellectual intelligence moderates motivation on employee performance in the company CV. Green Angelica of the significance value of 0.030, this study shows that employees can immediately understand clearly the direction given by the leadership.Keywords: Transformational Leadership Style, Motivation, Intellectual Intelligence and Employee Performance